VL Gehun 953: A high yielding, rust-resistant, winter x spring wheat (Triticum aestivum L.) derivative, suitable for organic hills as well as inorganic Plains of Uttarakhand state of India - Kant, Lakshmi; Pant, Subodh kumar; Jain, Sanjay Kumar; Raghu, Borehalli Rangaswamy; Pandey, Bhawani Dutt; Shankar, Daya; Mahanta, Dibakar; Jethi, Renu; Pattanayak, Arunava; Bankoti, Gopal Singh; Malkani, Laxmi Dutt (Journal of Cereal Research, 2025)
VL Gehun 953- a high yielding variety was released by Uttarakhandseed Sub-Committee and notified by Central Sub-Committee on CropStandards, Notification and Release of Variety for commercial cultivationunder irrigated inorganic production conditions of Uttarakhand Plainsand timely sown irrigated organic production situations of Uttarakhandhills. It recorded (3.34 tha-1) 7.46% higher grain yield compared tothe best check VL Gehun 907 under irrigated organic conditions ofUttarakhand hills. Likewise, it produced (4.47 tha-1) 6.93% higher grainyield compared to the best check PBW 343 under irrigated situationsof Uttarakhand Plains. It provided greater level of resistance to bothstripe and leaf rust and recorded average coefficient of infection (ACI)of 0.27 for stripe rust and 2.0 for leaf rust under artificial inoculationsituations, respectively. It contains 10.4 % average protein and 82.8kghl-1 hectoliter weight, therefore, possessing good quality for chapattimaking with good flour recovery. The large scale demonstrationsconducted in different districts of Uttarakhand has proved itsacceptability among the farmers. The spread of this variety in entireUttarakhand state (Hills under organic and Plains under inorganicconditions) is anticipated to enhance wheat productivity of the state.In addition, it would also help in curtailing the rust inoculum both inhills as well as plains of Uttarakhand owing to its better resistanceDOI.10.25174/2582-2675/2020/86682